Dataset associated with the manuscript: “Long-term compost amendment modulates wheat genotype differences in belowground carbon allocation, rhizosphere recruitment and nitrogen acquisition” - Kelly, Courtland; Fonte, Steven; Haddix, Michelle (Colorado State University. Libraries, 2021)
The implementation of soil health-promoting practices, such as cover crops and compost additions, has important implications for nutrient cycling regimes in agroecosystems. At the same time, plant belowground carbon (C) allocation patterns can influence nutrient cycling and availability in soil, but the effects may depend on the crop genotype and management practices in place. The relationship between root exudation, rhizosphere communities and the processes they regulate is likely influenced by a range of soil conditions, including soil organic matter (SOM) content, nutrient status, and overall soil biological activity, but such interactions remain poorly understood. To better understand the potential role of long-term soil management (that alters of SOM) and crop genotype in regulating rhizosphere microbial communities and associated nitrogen (N) cycling processes, we collected soils from two treatments in a 10-year field trial, one with high compost inputs (108.7 Mg ha-1 every 2 years) and a control (no nutrient inputs). We then used stable isotopes to measure belowground C allocation patterns in two genotypes of winter wheat (Triticum aestivum) with distinct rooting and exudation strategies. We also measured microbial community structure and function in the rhizosphere and quantified uptake of residue-derived N from 15N-labeled residues. We found an interactive effect between soil management and genotype, where the high-exudation genotype modified its exudation more in response to soil management and was relatively better at accessing residue N in the compost-amended soils than the low-exudation genotype. The high-exudation genotype also demonstrated selection of specific rhizosphere microbial taxa, with several taxa conserved across soil treatments. Our results suggest that the high-exudation strategy influences the microbial community, and this strategy is more successful in soils with higher SOM. Understanding the relationship between crop genotype, soil management, and microbial function can help inform crop production and breeding strategies in systems seeking to leverage improved soil health and biological nutrient cycling.
Format of data files – .csv; Location where data were collected – Fort Collins, CO; Time period during which data were collected - 2021; File Information – Total number of files: 3 Kelly_2021_Wheat_Genotype_Wheat.Genotype.Soil.Treatment _Datafile.csv – processed primary biogeochemical and plant data used for data analysis of referenced manuscript. README_Kelly_2021_Wheat.Genotype.Soil.Treatment.pdf – Description of data and associated publication Codebook.csv – description of variable names in Datafile.
Department of Soil & Crop Sciences
Keywords: cultivar; compost; microbial community; rhizosphere; Triticum aestivum